The Effect of Complex Skillful Exercises for developing The Endurance Of Distinguished fast Power for Youth Footballers - Mahmuod, Muwafaq Asaad; Asil, Fuoad Hamaad (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to know the extent of the effect of complex exercises for developing the speed of complex football performance on the members of his research sample. The researcher used the experimental approach to its suitability and the nature of the research problem. The research sample included (32) players divided into two control and experimental groups and in order to implement the research steps under the supervision of the researcher to conduct the pre-test of the research sample. After that the training curriculum was applied to the experimental group, then the post-test was conducted and after presenting, analyzing and discussing the results, he concluded that the complex exercises used helped to develop the speed of the complex skill performance with the Introduced to the experimental group and the researcher recommended to take advantage of the training curriculum prepared by the two researchers in building similar training curricula to develop offensive skills with other exercises similar to play and other times.